Інформатична компетентність викладача - Литвин, Андрій; Литвин, Оксана (Видавництво Львівської політехніки, 2015)
The author examines the components of informative competence of vocational school teacher in the context of increasing level of higher education informatization. Teacher competence involves a set of information, analysis, prognostic, projective, organizational, communication, orientation skills.
Keywords: інформатична компетентність; інформаційно-комунікаційні технології; педагогічні програмні засоби; електронні освітні ресурси